Viral Suppression Is Associated with HIV Treatment Self-Efficacy in a Cohort of Women in Washington, DC - Spence, Amanda Blair (AIDS Patient Care STDS, 2021)
The goal of HIV treatment is viral suppression as it is linked with improved health outcomes and decreased risk of viral transmission. We assessed the sociodemographic, behavioral, and patient–provider interaction associations with viral suppression with an administered survey to HIV-seropositive women in the metropolitan Washington, DC, site of the Women's Interagency HIV Study (WIHS) between 2017 and 2018. Logistic and mixed models were used to explore related factors between HIV viral suppression groups and HIV treatment self-efficacy, respectively. Higher HIV treatment self-efficacy and disclosure concerns were positively associated with viral suppression, while illicit drug use had a negative association. In mixed models, more health care provider trust was associated with higher HIV treatment self-efficacy, while depressive symptoms were associated with lower HIV treatment self-efficacy. Depression, illicit substance use, and HIV treatment self-efficacy are potentially modifiable factors that can influence viral suppression. Implementation studies are needed to determine whether interventions to manage depression or self-efficacy and improve trust in health care providers will influence treatment outcomes.